2015
DOI: 10.1021/acsbiomaterials.5b00292
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Multilayer Polysaccharide Membranes for Biomedical Applications

Abstract: Self-standing nanocomposite films based on biopolymers and functional nanostructures have been widely used due to their potential applications as active elements in biomedical devices. The coupling between chitosan (CHI) and alginate (ALG) multilayered films and magnetic nanoparticles (MNPs) allowed to fabricate magnetic responsive freestanding membranes with a high structural control along the thickness, using the layer-by-layer (LbL) methodology. The mechanical characterization evidenced a trend for an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…In particular, Fe 3 O 4 nanoparticles have received enormous interests and attracted the most attention due to its unique magnetic properties and biocompatibility. Therefore, capsules and MNPs have been combined in several biomedical applications, including targeted drug delivery, TE, magnetic thermotherapy (hyperthermia), magnetic resonance imaging, among others . Previously, we immobilized rhodamine after a modification with a silane (APTES) at the surface of the proposed MNPs to monitor the cellular uptake and then further assemble cells in a sheet‐like 3D structure .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Fe 3 O 4 nanoparticles have received enormous interests and attracted the most attention due to its unique magnetic properties and biocompatibility. Therefore, capsules and MNPs have been combined in several biomedical applications, including targeted drug delivery, TE, magnetic thermotherapy (hyperthermia), magnetic resonance imaging, among others . Previously, we immobilized rhodamine after a modification with a silane (APTES) at the surface of the proposed MNPs to monitor the cellular uptake and then further assemble cells in a sheet‐like 3D structure .…”
Section: Resultsmentioning
confidence: 99%
“…This can be overcome by the application of a mechanical stimulation based on a biomagnetic approach (Figure c). Different strategies based on biomagnetic biomaterial were developed, such as films, hydrogels, fibers, and 3D scaffolds . The combination of magnetic particles with polymeric biomaterials has demonstrated large potential for disease treatment and tissue repair, namely bone, muscle, nerve and cardiac tissue regeneration with external magnetic stimulation.…”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…8 Very recently, it was shown that the incorporation of magnetic nanoparticles within freestanding Alg/Chi multilayer films gave rise to an increase in the elastic moduli measured in the wet state by stress−strain measurements. 12 Probe-based indentation is a versatile method to study local mechanical properties of materials from the nanoscale to the macroscale. 13−15 Within this method, nanoindenter and atomic force microscopy (AFM) are the most used techniques.…”
Section: ■ Introductionmentioning
confidence: 99%